Functional characterisation of the TSC1-TSC2 complex to assess multiple TSC2 variants identified in single families affected by tuberous sclerosis complex - Dommering Charlotte; Baars Marieke; Maat-Kievit Anneke; Wessels Marja; Adriaans Alwin; Goedbloed Miriam; Sancak Őzgür; Nellist Mark; van den Ouweland Ans; Halley Dicky (BMC, 2008)
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal dominant disorder characterised by seizures, mental retardation and the development of hamartomas in a variety of organs and tissues. The disease is caused by mutations in either the TSC1 gene on chromosome 9q34, or the TSC2 gene on chromosome 16p13.3. The TSC1 and TSC2 gene products, TSC1 and TSC2, interact to form a protein complex that inhibits signal transduction to the downstream effectors of the mammalian target of rapamycin (mTOR). Methods We have used a combination of different assays to characterise the effects of a number of pathogenic TSC2 amino acid substitutions on TSC1-TSC2 complex formation and mTOR signalling. Results We used these assays to compare the effects of 9 different TSC2 variants (S132C, F143L, A196T, C244R, Y598H, I820del, T993M, L1511H and R1772C) identified in individuals with symptoms of TSC from 4 different families. In each case we were able to identify the pathogenic mutation. Conclusion Functional characterisation of TSC2 variants can help identify pathogenic changes in individuals with TSC, and assist in the diagnosis and genetic counselling of the index cases and/or other family members.